Come away with me - Brown, Karma (Don Mills, Ontario : MIRA Books, 2015)
"One minute, 26-year-old Tegan Lawson has everything she could hope for, including an adoring husband, Gabe, and a baby on the way. The next, a patch of black ice causes a devastating accident and Tegan's life is as shattered as the car they had to cut her out of. With the loss of her baby and her unbearable anger towards Gabe, who was driving that night, Tegan is drowning in grief. At Gabe's suggestion, she agrees to travel to three destinations from their 'life experiences' wish list. But Tegan soon learns grief follows you no matter how far away you go, and that acceptance comes when you least expect it. When things take a shocking turn in Hawaii, Tegan is forced to face the truth -- and she must decide if the life she has is the one she wants"-- from author's web site.
Includes reader's guide.
Keywords: Married people -- Fiction; Loss (Psychology) -- Fiction; Man-woman relationships -- Fiction; Travel -- Fiction; Domestic fiction